Plan táctico para la recuperación y normalización de la cartera para la empresa eficacia S.A (2023)
The tactical process of managing and collecting a company's receivables involves the efficient and effective management of accounts receivable to ensure that the company can recover money owed by its customers. The first step in this process is to establish clear policies and procedures for handling accounts receivable and to ensure that customers are aware of these policies. It is important that customers understand the terms of payment and the consequences of not meeting agreed-upon deadlines.